PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN PRODUK TELKOMSEL 4G” (STUDI KASUS PELANGGAN PRODUK KARTU TELKOMSEL DI KOTA BANDUNG TAHUN 2017): PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN PRODUK TELKOMSEL 4G” (STUDI KASUS PELANGGAN PRODUK KARTU TELKOMSEL DI KOTA BANDUNG TAHUN 2017) - Kusumahadi, Krishna (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
ABSTRACT Public is encouraged to use the latest 4G technology, businesses and the government must worked in fulfilling its needs . Telkomsel has become the largest provider of cellular products and internet data networks in Indonesia. Telkomsel provides 4G internet data network services with various advantages and an extensive network that is considered very capable to meet the needs of consumers in the current information technology era. However, currently the use of 4G internet data products still not attract a lot of consumer interest. In this study, we want to know how much Service Quality and Corporate Image have an effect on Consumer Loyalty, the users of Telkomsel 4G product services. The research method used in this study is a descriptive verification method, with data analysis techniques using path analysis. This research using 100 respondents, it was concluded that the variable Service Quality (X1), Corporate Image (X2) together had an influence on Customer Loyalty (Y) of 64.12%, the remaining 35.88% was influenced by other factors that did not entered in this study.